A DFT study of the effect of NNN Al atom on strength of Brönsted acid sites of HY zeolite. Issue 12 (12th August 2016) - Mo, Zhou-sheng; Li, Qiang; Qin, Yu-cai; Duan, Lin-hai; Zhang, Xiao-tong; Song, Li-juan
Abstract: A density functional theory study has been employed to investigate the effect of next-nearest-neighbours aluminium (NNN Al) atom on the acid strength of Brönsted acid site in Y zeolite. Additionally, the distribution of NNN Al atom was also studied. The obtained results show that thermodynamically, the favourable sites for location of NNN Al atom are the diagonal sites of the four-membered ring and meta-position of hexagon I. Furthermore, the increase of NNN Al atoms causes the nonlinear reduction of the strength of Brönsted acid sites. When the number of NNN Al atoms is greater than two, the increasing extent of acid strength is not obvious with the reduction in the number of NNN Al atoms. But the acid strength will increase linearly with the further reduce of the number of NNN Al atoms. Compared with deprotonation energy (ED ), ammonia adsorption energy (Eads ) could give a more reasonable measuring result for the acid strength.